Promotion Optimization: Effective Strategy to Increase Customer Interest in Gold Pawn at Bank Syariah Indonesia - Nurul Azizah Azzochrah (eCo-Fin, 2024)
This research delves into examining how promotional strategies impact customer interest in gold pawning services at Bank Syariah Indonesia KCP Bitung. Given the ever-changing market dynamics and evolving consumer preferences, the adaptability and innovation of Islamic banking institutions play a crucial role. The study concentrates on understanding how promotion influences customer interest in gold pawning, a service offering quick liquidity without requiring the sale of valuable assets. Through quantitative methods, data were gathered from 94 customers via questionnaires and analyzed using simple linear regression. The results indicate that promotional efforts significantly influence customer interest, explaining 61% of the variance. This underscores the significance of employing effective promotional strategies to enhance customer engagement and loyalty. The study identifies various promotional tactics, including advertising, sales promotions (such as discounts and coupons), personal selling (especially through social media influencers), public relations and publicity (e.g., press releases, event sponsorships, CSR activities), and direct marketing (e.g., mail, email, phone, social media). Each strategy's efficacy is supported by recent research, emphasizing the importance of coherent messaging in concise advertising for achieving higher response rates. The findings suggest that bolstering promotional endeavors can markedly increase customer interest and satisfaction, thereby fostering business expansion. Organizations are encouraged to prioritize strategic promotional activities to capitalize on their considerable influence on customer interest.